Keyakinan Makanan dalam Perspektif Keperawatan Transkultural pada Ibu Hamil di Wilayah Kerja Puskesmas Kartasura - Novitasari, Yuli, Arum Pratiwi, S.Kp., M.Kes, Sulastri, S.Kp., M.Kes (2016)
Cultural have a role on nutritional status for pregnant mother because had some belief, like taboo to consume some food that precisely have a good nutrition and needed by our body. One of culture in Indonesia that have something to belief about food is Javanese culture. This research aims to analys food belief who related with Java culture about recommendation and taboo to some food. Method of this research is kualitatif with etnographic approach. Respondent of five people selecte by consideration that the respondent have a lot of information for later interview by using recorder. The result shown that there have restriction and suggestion to certain food. Food that are prohobited form is goat meat, salty food, pineaple, durian, spicy food, herb, watermelon, sweet food and drink ice. That kind food belief can danger for pregnant mother and embryo. Whereas the recommended food is nutritional food, fish without scales and advice to drink plenty of water. Finding about this food had an effort to improve health. Keyword : Prohibition of food, food recommendation, pregnant mother